Chapter 1 A "C Odyssey" - Levine, Mark (Taylor & Francis, 2020)
The nutritional biochemist Alfred E. Harper was a member of the Food and Nutrition Board of the National Research Council/National Academy of Sciences for many years, and chair of the Food and Nutrition Board from 1978 to 1982. The scientific bases for many Recommended Dietary Allowances (RDA) were prevention of deficiency with a margin of safety, often determined from depletion-repletion studies or balance experiments. As nutritional science has grown, and policy needs have changed, limitations of RDAs were recognized. Fundamental biochemical kinetics concepts can be the foundation for nutrient recommendations. Bioavailability experiments showed plasma and tissue concentrations were tightly controlled with oral administration of ascorbic acid. Reabsorption would be predicted in proximal renal tubules, concurrent with sodium-dependent vitamin C transporter1 localization. Accelerated ascorbic acid utilization in disease states may be a new frontier that can lead to discoveries for roles of ascorbic acid in disease treatment.